Understanding Teachers of PJOK Towards Physical Education and Authentic Assessment of Elementary School in Kotabumi - Cahyo Wibowo; Sanfia Tesabela Messakh; Pius Bimanto Yoke (Journal Physical Education, Health and Recreation, 2021)
Physical education, sports and health (Physical Education) is a subject in which students are given the opportunity to learn through systematic physical, sport and health activities. Physical education learning achievement carried out in elementary schools can be influenced by several supporting factors, one of which is determined by the ability of PJOK teachers in teaching and assessing students' abilities. Authentic assessment is an assessment that is measured significantly from student learning outcomes in the realm of attitudes, knowledge and skills. The purpose of this study was to determine the understanding of PJOK teachers about physical education and authentic assessment in the city of Kotabumi, North Lampung. This type of research uses quantitative descriptive with the number of respondents as many as 30PJOK teachers who are members of the KKG in Kotabumi. The data collection was carried out in January-May 2021 via google form. The calculation of the data is done by categorizing the data into categories of very understanding, understanding, not understanding, and very not understanding. The results obtained are the understanding of physical education teachers about physical education and sports by 43% very understanding and 57% understanding and understanding of physical education teachers about the purpose of physical education and sports by 37% not understanding. PJOK teachers' understanding of the application of authentic assessment is that 53% understand the knowledge aspect, 70% understand the attitude aspect and 45% do not understand the skill aspect. Conclusion: PJOK teachers' understanding of the implementation and objectives of physical education learning is in a good category. PJOK Elementary School teachers' understanding of authentic assessment is in the good category. However, in understanding the application of the three aspects of authentic assessment, it has not been maximized, because PJOK teachers are still carried away with the conventional assessment system.